Study on the effect of time constant on flow and temperature controllability: article - Abdul Razak, Farah Diyana; Ishak, Abdul Aziz (2017)
This research project is to study on the effect of time constant on the flow and temperature controllability. This can be achieved by doing an open loop test, followed by the performance test using three different tuning rules, which are Ziegler-Nicholes, Cohen Coon and Takahashi. From the tuning method, value of the P – I – D is obtained. Thus, performance test such as load disturbance test and set point test is done to see which method gives the best performance. Tangent analysis is a conventional method used to analyzed an open loop step reponse curve. It is done by drawing a tangent line at the steepest point of the step response curve. In this research project, numerical analysis is used as it is much faster in obtaining data compared to tangent analysis. The process dynamics such as dead time and response rate can be obtained from the analysis. Meanwhile, values of the response rate, RR, and the dead time, Td, differs comparing flow and temperature, which in turn, resulted in different values of P’s and I’s of different tuning method (Ishak & Ahmad, 2002). In this research paper, the time constant and settling time is observed to see which tuning rules gives the best performance based on the time constant as time constant affects the settling time.